Watercore in Apple Landraces (Malus domestica Borkh.) as a quality indicator - Arnal, Alberto (Revista de Ciencias Agrícolas, 2021)
Watercore is the presence of a vitrified texture intruded in the pulp of the fruit. It is found in fruits from different genus and families; and it has been studied in apples. Watercore was described, in apples, as a texture with differential sensorial characteristics in relationship with the ordinary pulp, and its presence is currently considered a defect in apple production, causing economic losses. In this study, it is described as a dichotomous descriptor. We analysed 641 apples from a region belonging to Central Spain (Guadarrama mountain range and the close Tagus Basin River); it was found that around 30% of those apples shown this characteristic, being practically all of them from landraces. Studies related to traditional cultivars do not analyze such characteristic, considered up today as a defect. Nevertheless, we discuss that watercore can have some potential as it gives to apple a distinct appearance and aroma, all of them of value in differential quality and international seal protection. As a result, we conclude our preliminary analysis that it is highly recommended to take into consideration watercore as a descriptor in apple characterizations.